Rancang Bangun Sistem Informasi dan Bisnis (Study Kasus : Ngemil Snacking) - Akbar Rozaq Rais, Nendy; Feri Efendi, Tino; Bagoes Pakarti, Moch (Jurnal Informatika, Komputer dan Bisnis (JIKOBIS), 2023)
The internet makes almost everything easier, such as communication, online learning and trading. Ngemil Snacking is engaged in production and sales providing various kinds of snack products. In terms of sales at Ngemil Snacking, currently it is still done conventionally, namely selling products manually and online to promote its products, but recording sales transactions is still done manually. Recording transactions manually makes it difficult for traders to handle a lot of sales, it uses a lot of paper to record them, the data will be wrong if one of the sales reports is missing, there may be an error in calculating the money. Based on the problems above, an information system is needed that can help with snacking. The information system that will be created is a web-based information system, where in this system customers can access information on what products are being sold and make purchases online, and customers can also see order status. This research method is the SDLC development method for building and developing websites. The result of this research is a design for building a website-based information system using the PHP and MySQL programming languages.